Gymnastic judges benefit from their own motor experience as gymnasts - Bardel, A. P. (Research Quarterly for Exercise and Sport, 2012)
Gymnastic judges have the difficult task of evaluating highly complex skills. My purpose in the current study was to examine evidence that judges use their sensorimotor experiences to enhance their perceptual judgments. In a video test, 58 judges rated 31 gymnasts performing a balance beam skill. I compared decision quality between judges who could perform the skill themselves on the balance beam (specific motor experience = SME) and those who could not. Those with SME showed better performance than those without SME. These data suggest that judges use their personal experiences as information to accurately assess complex gymnastic.